Tripodal penta(p-phenylene) for the biofunctionalization of alkynyl-modified silicon surfaces. - Sánchez-Molina, María; Díaz-Morilla, Amelia; Valpuesta-Fernández, María; Contreras-Cáceres, Rafael; López-Romero, Juan Manuel; López-Ramírez, María Rosa (Elsevier, 2018)
Here we report the optimization on the covalent grafting methodology of a tripod-shaped penta(p-phenylene), 1, on alkynyl-terminated silicon surfaces, and the incorporation of an active theophylline derivative, 2, for the specific immobilization of proteins. The tripodal molecule presents azide-terminal groups to be attached onto a silicon surface containing an alkynyl monolayer. Initially, compound 1 has been covalently incorporated on alkynyl-terminated Si wafers, by the copper catalyzed alkyne-azide 1,3-dipolar cycloaddition (CuAAC, a click reaction). The tripod density on the silicon surface is tuned by performing the CuAAC reaction at different concentrations of 1, as well as under different experimental conditions (T, base, copper source, shaking). Then, tripod 1-modified surface has also been biofunctionalized with 2. The effective preparation of this silicon-modified surface allowed us to study the streptavidin immobilization on the surface. Characterization of the different surfaces has been carried out by X-Ray Photoelectron Spectroscopy (XPS), Atomic Force Microscopy (AFM) and Bright-Field Optical Transmission Microscopy (Confocal) techniques. We also include density functional theory (DFT) analysis of the organic structures to confirm the height-profile and the tripod-surface relative configuration extracted from AFM images.
Keywords: Nanoestructuras; Silicio; Tripodal phenylene; Silicon surface; Click reaction; Nanostructuration; Theophylline; Bifunctionalization